Electrostatic Self-Assembly of CdS Quantum Dots with Co9S8 Hollow Nanotubes for Enhanced Visible Light Photocatalytic H2 Production - Yuqing Yan; Yonghui Wu; Chenggen Lu; Yu Wei; Jun Wang; Bo Weng; Wei-Ya Huang; Jia-Lin Zhang; Kai Yang; Kangqiang Lu (Molecules, 2024)
CdS quantum dots (CdS QDs) are regarded as a promising photocatalyst due to their remarkable response to visible light and suitable placement of conduction bands and valence bands. However, the problem of photocorrosion severely restricts their application. Herein, the CdS QDs-Co9S8 hollow nanotube composite photocatalyst has been successfully prepared by loading Co9S8 nanotubes onto CdS QDs through an electrostatic self-assembly method. The experimental results show that the introduction of Co9S8 cocatalyst can form a stable structure with CdS QDs, and can effectively avoid the photocorrosion of CdS QDs. Compared with blank CdS QDs, the CdS QDs-Co9S8 composite exhibits obviously better photocatalytic hydrogen evolution performance. In particular, CdS QDs loaded with 30% Co9S8 (CdS QDs-30%Co9S8) demonstrate the best photocatalytic performance, and the H2 production rate reaches 9642.7 μmol·g−1·h−1, which is 60.3 times that of the blank CdS QDs. A series of characterizations confirm that the growth of CdS QDs on Co9S8 nanotubes effectively facilitates the separation and migration of photogenerated carriers, thereby improving the photocatalytic hydrogen production properties of the composite. We expect that this work will facilitate the rational design of CdS-based photocatalysts, thereby enabling the development of more low-cost, high-efficiency and high-stability composites for photocatalysis.